(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the lexico-stylistic features of speech communication in literary translations. The study discusses how the semantic and stylistic features of speech communication are preserved or changed during the translation of literary texts. The main attention is paid to the translator's lexical and stylistic choices, contextual adaptation in the process of communication, as well as cases of loss or change of meaning. The article examines the linguistic features of literary translations based on discursive and corpus analysis, and also analyzes the cultural and communicative aspects of translation. The research results contribute to a deeper understanding of linguistic and stylistic problems in the process of literary translation and are of great importance for the theory and practice of translation.